Three 2‐(methysulfanyl)nicotinamides. (17th February 2013) - Gomes, Ligia R.; Low, John Nicolson; Wardell, James L.; Pinheiro, Alessandra C.; Mendonça, Thais C. N. de; Souza, Marcus V. N. de
Abstract : The molecular conformations of three N ‐alkyl‐2‐(methylsulfanyl)nicotinamide derivatives, namely N ‐cyclohexyl‐2‐(methylsulfanyl)nicotinamide, C13 H18 N2 OS, (I), N ‐isopropyl‐2‐(methylsulfanyl)nicotinamide, C10 H14 N2 OS, (II), in which there are two molecules in the asymmetric unit which were chosen to form a hydrogen‐bonded pair, and N ‐(2‐hydroxyethyl)‐2‐(methylsulfanyl)nicotinamide dihydrate, C9 H12 N2 O2 S·2H2 O, (III), are compared with those of four unsubstituted N ‐alkylnicotinamide compounds. The substituted compounds show a higher degree of torsion of the pyridine ring with respect to the amide group than do the unsubstituted compounds, with dihedral angles in the range 40–60° for the former and 20–35° for the latter. In (I) and (II), the supramolecular structure is defined by amide‐N to carbonyl‐O chains. In (III), the nicotinamide molecules are linked by hydrogen bonds to two water molecules resulting in two linked chains of rings which form the three‐dimensional network.